Gender empowerment approaches: interventions through Qanun number 6 of 2009 in Aceh, Indonesia - Al Aro, A.S. (EDP Sciences, 2021)
Aceh is a province in Indonesia that makes Islamic sharia as one of the bases in policy determination, one of which is policies related to gender empowerment. It is interesting to be studied about the condition of gender empowerment in Aceh, especially after the ratification of Qanun Aceh No. 6 of 2009 on Women Empowerment and Protection. The study used descriptive qualitative analysis of secondary data obtained from BPS Aceh Province. The results showed that the implementation of Qanun No. 26 of 2009 related to the empowerment and protection of women is still not done to the maximum, either explicitly or implicitly. This is evidenced by the condition of Aceh Gender Empowerment Index which has a volatile trend from 2010-2019 with an index ranging from 52.06 to 67.4. The trend is strongly influenced by the three components of GEI, namely women's involvement in parliament, women's involvement as professionals, and women's income donations. The involvement of women in parliament still does not meet the minimum figure of 30. The involvement of women as professionals has a volatile trend. Meanwhile, women's income contributions always increase every year. Â© The Authors, published by EDP Sciences.